Analisis Pengaruh Modal Usaha dan Pemahaman Akuntansi Terhadap Perkembangan Bisnis Kuliner UMKM di Kawasan Industri Terbesar di Indonesia (Studi Kasus Kabupaten Karawang) - February Leonardo Zulkarnain; Karina Maunita Dewi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The study focused on micro, small, and medium-sized enterprises (MSMEs) in the culinary sector of Karawang Regency, which is Indonesia's largest industrial region. The aim of the research was to assess how capital ownership and accounting knowledge affect the growth of MSMEs in this sector, given the limited access to capital for these enterprises. This study utilized a quantitative approach, gathering primary data through questionnaires. A total of 100 respondents participated in this research. The analysis was carried out using multiple linear regression with SPSS version 27. The results indicate that both capital ownership and understanding of accounting, either individually or simultaneously, influence the development of the culinary business sector among MSMEs in Karawang Regency.